Assessment of CO2 Emission by Tractor Engine at Varied Control Settings of Fuel Unit (Agricultural Engineering, 2021)
The paper presents results of experimental studies concerning CO2 emission of S-4003 diesel engine Ursus C-360 at a variable fuel injection advance angle and opening pressure of injectors. Measurements were made on the dynamometric stand on the test bench. The engine operated according to the load characteristic at two characteristic rotational speeds i.e., at the maximum torque velocity (1600 rpm) and at the rated speed (2200 rpm). In each measurement point of load characteristics, CO2 concentration was measured in exhaust gases with the use of exhaust gases analyser M-488 Multigas Plus. For a more detailed analysis of the CO2 content in exhaust gases, additional change of O2 level emission was presented, which in the biggest amount combines elementary carbon included in fuel during combustion. The studies showed the CO2content reduction in exhaust gases at the reduced (by 3º of crankshaft rotations) fuel injection advance angle in comparison to the nominal angle by 4.5% at the rotational speed of 1600 rpm and by 5.7% at the speed of 2200 rpm (the average values for all measurement points of load - brake horsepower of engine). Similarly, CO2 concentration decrease in exhaust gases of the investigated engine was reported for the increased (by 1.5 MPa) opening pressure of injectors in comparison to the nominal pressure, on average by 9.8% for the speed of the maximum rotational moment and by 4.5% for the rated speed.